Conversion of Magnesium from Bittern with Sodium Phosphate Addition through Precipitation Process - Dodik Hendra Saputra; Evlyansa Bunga Rizka Ananda; Dyah Suci Perwitasari; Caecilia Pujiastuti (Jurnal Serambi Engineering, 2025)
Bittern, a by-product of the salt production process, contains high concentrations of magnesium ions, which have significant economic potential and use value in various fields. The objective of this study is to recover magnesium from bittern using sodium phosphate (Na₃PO₄) through the process of chemical precipitation. The reaction between magnesium and phosphate produces magnesium phosphate compounds, which are commercially valuable in the industrial and agricultural sectors. The present study analysed the effect of several process parameters, including pH, temperature and reaction time, on magnesium recovery efficiency. Optimum conditions were obtained at pH 9 with the addition of a 15% concentrated Na₃PO₄ solution. The precipitate formed was then characterised using X-Ray Fluorescence (XRF) to confirm the presence of magnesium phosphate. The findings demonstrate that this method facilitates the effective recovery of magnesium from bittern, exhibiting both high efficiency and good selectivity. This approach has the potential to provide a sustainable solution for the treatment of bittern effluent, whilst concomitantly producing environmentally friendly value-added products.